Sulfur K-edge XAS and DFT Studies on Ni(II) Complexes with Oxidized Thiolate Ligands: Implications for the Roles of Oxidized Thiolates in the Active Sites of Fe and Co Nitrile Hydratase - Dey, Abhishek (2007)
S K-edge XAS data on a series of Ni(II) complexes with thiolate (RS(−)) and oxidized thiolate (RSO(2)(−)) ligands are used to quantify Ni-S bond covalency and its change upon ligand oxidation. Analyses of these results using geometry optimized DFT calculations suggest that the Ni-S σ bonds do not weaken on ligand oxidation. Molecular orbital analysis indicates that these oxidized thiolate ligands use filled high lying S-O π* orbitals for strong σ donation. However, the RSO(2)(−) ligands are poor π donors as the orbital required for π interaction is is used in the S-O σ bond formation. The oxidation of the thiolate reduces the repulsion between electrons in the filled Ni t(2) orbital and the thiolate out of plane π-donor orbital leading to shorter Ni-S bond length relative to a thiolate donor. The insights obtained from these results are relevant to the active sites of Fe and Co type nitrile hydratases (Nhase) that also have oxidized thiolate ligands. DFT calculations on models of the active site indicate that while the oxidation of these thiolates has a major effect in the axial ligand binding affinity of the Fe type Nhase (where there is both σ and π donation from the S ligands), it has only a limited effect on the sixth ligand binding affinity of the Co type Nhases (where there is only σ donation). These oxidized residues may also play a role in substrate binding and proton shuttling at the active site.